Conceptual design of the radial gamma ray spectrometers system for α particle and runaway electron measurements at ITER. (18th May 2017) - Nocente, M.; Tardocchi, M.; Barnsley, R.; Bertalot, L.; Brichard, B.; Croci, G.; Brolatti, G.; Di Pace, L.; Fernandes, A.; Giacomelli, L.; Lengar, I.; Moszynski, M.; et al.
Abstract: We here present the principles and main physics capabilities behind the design of the radial gamma ray spectrometers (RGRS) system for alpha particle and runaway electron measurements at ITER. The diagnostic benefits from recent advances in gamma-ray spectrometry for tokamak plasmas and combines space and high energy resolution in a single device. The RGRS system as designed can provide information on α   particles on a time scale of 1/10 of the slowing down time for the ITER 500 MW full power DT scenario. Spectral observations of the 3.21 and 4.44 MeV peaks from the 9 B e ( α, n γ ) 12 C   reaction make the measurements sensitive to α   particles at characteristic resonant energies and to possible anisotropies of their slowing down distribution function. An independent assessment of the neutron rate by gamma-ray emission is also feasible. In case of runaway electrons born in disruptions with a typical duration of 100 ms, a time resolution of at least 10 ms for runaway electron studies can be achieved depending on the scenario and down to a current of 40 kA by use of external gas injection. We find that the bremsstrahlung spectrum in the MeV range from confined runaways is sensitive to the electron velocity space up to E ≈ 30 –40 MeV, which allows for measurements of the energy distribution of the runaway electrons at ITER.